Impact of External Debt on Aggregate Investment and Productivity in Pakistan - Rafiq Mansoor; Shumaila Nawaz; Aqeel Mansoor; Asma Imran (Al-Qanṭara, 2025)
Investment and factor productivity are important economic indicators to explain the economic prosperity of the economy. This intellectual effort is executed in Pakistan economy, to find the relationship between investment & debt, and between factor productivity and debt. The relationship between (investment & debt and between factor productivity & debt) is estimated by using annual time series data from 1979 to 2020 under controlled policy variables like, interest rate, consumer price index, trade openness, fiscal development, fiscal deficit, population and human capital. The auto regressive distributed lag model is used for empirical quantification and augmented dicky fuller test is used to test stationarity of data. The findings suggest that debt, fiscal deficit, financial development, population growth and interest have negative relationship with investment whereas inflation, employed per person income and trade openness has positive impact on the investment. The other findings provide the evidence that debt, interest rate, has negative impact on productivity and human capital, fiscal development, fiscal deficit and inflation has positive impact on productivity. The findings suggest that there is need to curtail the debt in long run to increase the investment and productivity. Government needs to increase its revenue with influencing the domestic interest rate which leads to reduction in investment and influence the output of the economy.